PENGARUH FAKTOR KEUANGAN DAN FAKTOR NON KEUANGAN TERHADAP PENGUNGKAPAN OPINI GOING CONCERN: Ukuran Perusahaan sebagai variabel moderasi - Nurul Hidayati (Lembaga Penelitian Universitas Trisakti, 2020)
This study uses a research model to obtain empirical evidence about the effect of profitability, company growth and audit lag on going concern opinion moderated by company size. The variables used in this research model are going concern opinion, profitability, company growth, audit lag and company size. The research sample consisted of mining companies listed on the Indonesia Stock Exchange in the period 2016 - 2018. Based on sampling using the purposive sampling method, the samples used in this study were 34 companies with a three-year period producing 102 sample units. Data analysis was performed by logistic regression analysis, with a significance value of 5%. The results of the study concluded that profitability has a negative effect on going concern opinion. Meanwhile, company growth and audit lag did not significantly influence going concern opinion.